Design, synthesis, and structure-activity relationships of novel imidazo[4, 5-c]pyridine derivatives as potent non-nucleoside inhibitors of hepatitis C virus NS5B. Issue 9 (15th May 2018) - Liu, Moyi; Xu, Qiaoling; Guo, Su; Zuo, Ruixi; Hong, Yue; Luo, Yong; Li, Yingxiu; Gong, Ping; Liu, Yajing
Graphical abstract: Three series of novel imidazo[4, 5-c]pyridine derivatives based on the structure of tegobuvir have been designed, synthesized and evaluated for their anti-HCV activity. Highlights: Three series of compounds were synthesized and evaluated for their anti-hepatitis C virus activities. The most promising compound 3 exhibited an EC50 value of 1.163 nM in a subgenomic replicon assay. The pharmacokinetics of compound 3 was within a desirable range. Abstract: The hepatitis C virus (HCV) NS5B polymerase is an attractive target for the development of novel and selective inhibitors of HCV replication. In this paper, the design, synthesis, and preliminary SAR studies of novel inhibitors of HCV NS5B polymerase based on the structure of tegobuvir have been described. The efforts to optimize the antiviral potency and reduce the treatment side effects with respect to genotype 1b resulted in the discovery of compound 3, which exhibited an EC50 of 1.163 nM and a CC50 >200 nM in a cell-based HCV replicon system assay. Additionally, testing for inhibition of the hERG channel showed a marked improvement over tegobuvir and the pharmacokinetic properties of compound 3 indicated that it was worthy of further investigation as a non-nucleoside inhibitor of HCV NS5B polymerase.